Trauma mamilar: causas e tratamento uma revisão da literatura - Souza, Débora Carina de (Universidade do Vale do Rio dos Sinos, 2011)
This research has the objective of identifying and analyzing the factors which cause nipple trauma and its available treatments. It is based on revision of published material from 2001 through 2010, which was found online on the systems LILACS, SIELO, BDENF, MEDLINE and Academics Google. It was found that the newborn has to be trained in the right technique for positioning and sucking, to avoid nipple trauma. Therefore, it is necessary to emphasize the mothers’ orientation, from pregnancy, up to the exit from the maternity, as well as the training of the professionals involved in the promotion of the exclusive breastfeeding. As treatment, it is advised the chosen of the humid approach with the utilization of lanolin, which has shown positive results. It is also in test, the use of low intensity laser bean, which has showed a significant improvement after the application, even though more research for this method is still needed.
Keywords: Amamentação; Trauma mamilar; Saúde da mulher; Breastfeeding; Nipple trauma; Woman health